THU0363 Pilot Study of TOCILIZUMAB in Patients with Erdheim-Chester Disease. (10th June 2014) - Berti, A.; Guglielmi, B.; Biavasco, R.; Gelpi, M.; Campochiaro, C.; Cavalli, G.; Tomelleri, A.; Ferrarini, M.; Sabbadini, M.G.; Dagna, L.
Abstract : Background: Erdheim-Chester disease (ECD) is a rare, systemic disorder of unknown etiology, characterized by tissue infiltration with CD68+, CD1a- foamy histiocytes. ECD is still a chronically debilitating disease without a gold-standard treatment. Evidence is accumulating that inflammatory cytokines and chemokines are responsible for histiocytes recruitment and activation. In particular, recent data showed that IL-6 is strongly expressed in ECD lesions and increased serum levels of IL-6 have been implicated in the systemic manifestations observed in ECD. Objectives: We intend to assess the efficacy and safety of IL-6 blockade in patients with ECD. Methods: We are conducting an open-label, single-arm, phase II, prospective, pilot study of tocilizumab (TCZ) in ECD (ClinicalTrials.gov NCT01727206 ; Eudra-CT 2012-003151-11). We planned to treat 6 patients (with contraindications or unresponsive to IFN-α) with the IL-6 receptor inhibitor TCZ 8 mg/kg monthly. We are collecting clinical, laboratory and radiological data, by means of total-body computed tomography (CT) scan, Technetium-99m methylene diphosphonate (99mTc-MDP) bone-scan, fluorine-18-2-fluoro-d-glucose positron emission tomography (FDG-PET), brain and cardiac Magnetic Resonance Imaging (MRI). We are also evaluating the levels of pro-inflammatory cytokines and chemokines before, during and after therapy, in order to evaluate the network of soluble factors shown to be involved in ECD pathogenesis and its possible modulation after TCZ treatment. The Mann-Whitney U test for unpaired was chosen to compare data obtained from ECD patients and controls. The significance level was set at 0.05 (two-tailed p distribution). Results: We present data from per protocol interim analysis on the first three patients who completed the protocol so far. All patients achieved significant improvement of all the clinical manifestations and laboratory findings (follow up at 12 months). Repeated whole-body CT scans, FDG-PET imaging and 99mTc-MDP bone scans confirmed the clinical and biochemical improvement in all patients. Cardiac MRI of the patient who had cardiovascular involvement showed an improvement of the diastolic function. However, the single patient who had CNS involvement had neurological progression, albeit showing improvement of other disease sites. During follow-up, we demonstrated a progressive reduction of circulating pro-inflammatory cyto-chemokines levels found to be increased before treatment. Plasma levels of IL-6 increased in all patients after the first infusion, as already shown in patients with other diseases treated with TCZ. Conclusions: Although these data must be completed with the final analysis and possibly by larger studies, the interim analysis of the trial support the efficacy and safety of IL-6 targeting with TCZ in ECD patients, in particular when CNS is not involved. Of interest, TCZ showed beneficial effects on ECD cardiovascular involvement, which has been shown to be poorly responsive to most currently available treatments. References: Stoppacciaro A et al. Arthritis Rheum. 2006 Dec;54(12):4018-22. Dagna L et al. Rheumatology (Oxford). 2010 Jun;49(6):1203-6. Mossetti G et al. Clin Exp Rheumatol. 2003 Mar-Apr;21(2):232-6. Arnaud L et al. Blood. 2011 Mar 10;117(10):2778-82. doi: 10.1182/blood-2010-06-294108. Acknowledgements: This work was supported by a research grant from the Italian Ministry of Health to Lorenzo Dagna (GR-2009-1594586). Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5705